THE PHOSPHATE SOLUBILIZING POTENTIAL OF CITROBACTER FREUNDII UNDER VARIOUS PHYSICOCHEMICAL CONDITIONS: Life Science-Microbiology - RATHORE, PRAGYA; SHAH, PRATIK; CHANDOK, HARSHPREET; PATEL, SATYENDRA (International Journal of Life Science and Pharma Research, 2012)
There are considerable evidences that support the specific role of phosphate solubilization in the enhancement of plant growth by phosphate solubilizing microorganisms. In this regard we had isolated a bacterial stain which could solubilize phosphate to a considerable level, hence we selected the organism and subjected it to further studies involving different parameters. The effects of different conditions on phosphate solubilization by Citrobacter freundii from local soils of Indore were studied. The optimum concentration of phosphorus for maximum % solubilization was found to be 50 mg% for tricalcium phosphate (TCP). Studies on effect of temperature and shake and static conditions revealed that the organism gives maximum solubilization of phosphorus at 28°C ± 2°C and under static condition of incubation. Maximum solubilization of phosphorus was reported between pH ranges 7-8.